Personality Traits Recognition System - Mohammad Nasir, Mohammad Arash (Universiti Teknologi PETRONAS, 2021)
Personality traits are defined as reflecting people's characteristics, patterns of thoughts, behaviours, and feelings. There are five essential personality traits: Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. Scientists have discovered that personality traits can be recognised using questionnaire assessment and human expert in the earlier era. Since then, it has been improved from day by day. From the assessment method, the result from the analysation is less accurate and difficult to interpret as the candidates can manipulate the score to attract employers. Furthermore, human expert required experience and the training is costly. Lastly, another weakness of human expert is that recognition can be very subjective as several factors such as gender, age, and race can affect detection accuracy. From the problem observed, the automatic personality traits prediction system has received attention from the researchers. One of them is using deep learning to perform the computation of personality traits used in this project.